P07 Interleukin response to cyclical mechanical stretch with models of different neonatal ventilation modes. (24th May 2017) - Harris, C; Rushwan, S; Wang, W; Thorpe, S; Thompson, C; Peacock, J; Knight, M; Gooptu, B; Greenough, A
Abstract : Aims: A follow-up study of a randomised trial, the United Kingdom Oscillation Study (UKOS) comparing conventional ventilation (CMV) to high frequency oscillation ventilation (HFOV) immediately after birth, (1) demonstrated lung function was significantly better at age 11–14 years in the HFOV group. (2) During CMV, the inflation volumes are approximately two to three times larger than those during HFOV. Cyclical mechanical stretch (CMS) applied to A549 cells (type II alveolar cell analogues) has been shown to result in interleukin-8 release which increases with increasing basement membrane stretch. (3) We, therefore, hypothesised that during 'CMV' there would be greater interleukin release compared with 'HFOV', from type II alveolar cells. Methods: A549 cells were grown in Dulbecco's modified Eagle's medium (DMEM) on flexible collagen based plates. Adherent cells were subjected to CMS conditions modelling CMV or HFOV using a Flexcell 4000T machine. Conditioned medium was analysed by ELISA to determine IL-6 and IL-8 levels following CMS for two and four hours. The results were compared with levels measured from control A549 cells that were unstretched or constantly stretched to 5% and 20% over the same time course. Results: The mean fold increase of IL-8 release compared with the un-stretched control samples was higher in the 'CMV' compared with the 'HFOV' model at two hours (1.59, standard deviation (SD) 0.17 versus 0.91, SD 0.31, p<0.001) and four hours (2.55, SD 0.82 versus 1.45 SD 0.16, p=0.001). The mean fold increase of IL-6 release compared with the un-stretched control samples were higher at four hours in the 'CMV' compared with the 'HFOV' model (1.36, SD 0.13 versus 1.15, SD 0.06, p<0.001). Conclusion: Conditions modelling CMV resulted in greater interleukin release in lung epithelial cells relative to those modelling HFOV. We propose that this may disrupt lung development in neonates supported by CMV rather than HFOV resulting in inferior lung function at follow-up.